2004
DOI: 10.1111/j.1464-410x.2003.04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Can leakage at the vesico‐urethral anastomosis be predicted after radical retropubic prostatectomy?

Abstract: assess vesico-urethral integrity before catheter removal. RESULTSOf the 275 patients, 75% and 89% had cystography before 8 and 10 days after RRP, respectively; 71% of patients had no leak on cystography and were catheter-free at 8 days. Eighty-four leaks were identified, of which 25 (9.6%) were moderate or large. Previous transurethral prostatectomy, ischaemic heart disease, blood loss, mucosal eversion and preservation of the prostatic urethra were significant risk factors for developing a leak and were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 10 publications
5
31
1
Order By: Relevance
“…Although the present study did not aim to predict postoperative anastomotic urine leak, as other studies have attempted [5,12,13], there are several findings that are consistent with these previous studies. Among patients with anastomotic urine leak, an increased rate of bladder neck reconstruction was found.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although the present study did not aim to predict postoperative anastomotic urine leak, as other studies have attempted [5,12,13], there are several findings that are consistent with these previous studies. Among patients with anastomotic urine leak, an increased rate of bladder neck reconstruction was found.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with studies showing that blood loss is a significant predictor of urinary extravasation on postoperative cystogram [12], as well as with studies suggesting the proposed mechanism of pooled blood in the pelvis exerting distraction forces on the vesico-urethral anastomosis causing partial separation and anastomotic leakage. Indeed, O'Malley et al [14] recently showed that transabdominal ultrasound measurement of pelvic haematoma volume predicted extravasation on cystography almost perfectly (area under the curve of receiver-oprator characteristic = 0.99).…”
Section: O N G -T E R M R E L E V a N C E O F P O S T O P E R A T Isupporting
confidence: 91%
See 2 more Smart Citations
“…However, obesity and excessive bleeding were associated with decreased visibility of the bladder neck, hampering suture placement in urethro-vesical anastomosis [14] . As a surgical factor, non-eversion of the mucosa was suggested for tighter anastomosis instead of eversion [15] .…”
Section: Urine Leakagementioning
confidence: 99%